Undocumented rural workers of Tamaulipas in United States agriculture - Izcara Palacios, Simón Pedro (Libros UAT, 2018)
Since the late nineteenth century, US agricultural entrepreneurs have sought to increase the profitability of their farms through the employment of foreign labor, disciplined and non-unionized. A century of policies to criminalize illegal immigration and allow the employment of undocumented labor have generated an extremely irregular agricultural labor market. More than half of the workers employed in American agriculture are undocumented and made use of fraudulent documentation to obtain their employment.